2018
DOI: 10.1016/j.survophthal.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Infectious crystalline keratopathy

Abstract: Infectious crystalline keratopathy was first reported by Gorovoy and colleagues in 1983 when they identified bacteria colonizing a cornea after a penetrating keratoplasty. Subsequent cases have elaborated on the organisms responsible and the management outcomes. Patients present with a white or gray branching opacity originating from an epithelial defect, commonly after a penetrating keratoplasty. Local immunosuppression contributes to the quiescent nature and the limited inflammatory response associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 134 publications
(161 reference statements)
0
54
0
7
Order By: Relevance
“…First described by Gorovoy et al, 1 infectious crystalline keratopathy is a rare, chronic and indolent pathology in which a characteristic plaque-shape interlamellar arboriform and crystalline bacterial stromal infiltrate is observed in absence of an apparent inflammation in cornea or anterior chamber 2, 3. We present three cases of infectious crystalline keratopathy in patients with different risk factors, where a pharmacological treatment led to the disappearance of the symptoms.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…First described by Gorovoy et al, 1 infectious crystalline keratopathy is a rare, chronic and indolent pathology in which a characteristic plaque-shape interlamellar arboriform and crystalline bacterial stromal infiltrate is observed in absence of an apparent inflammation in cornea or anterior chamber 2, 3. We present three cases of infectious crystalline keratopathy in patients with different risk factors, where a pharmacological treatment led to the disappearance of the symptoms.…”
Section: Introductionmentioning
confidence: 72%
“…Many microorganisms that cause crystalline keratopathy have been reported,2, 3, 4, 5, 6, 7, 8 although viridans-type streptococci are the most frequently isolated 3, 4, 9. The identification of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…We used fluorochinolones as a postoperative treatment for only a week, so we do not consider this as a potential etiology for the crystalline keratopathy in our cases. The main cause for crystalline keratopathy is reported due to an infectious etiology [6]. The literature review revealed one case report of unknown infection as well as one case of Fusarium solani positive crystalline keratopathy within 3 and 4 weeks of CXL, respectively [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…If topical and/ or intrastromal antibiotics/ antifungals are unsuccessful, Nd:YAG laser can be used to disrupt the microbial biofilm. Ultimately, patients will need to undergo keratoplasty [ 10 ].…”
Section: Discussionmentioning
confidence: 99%